Power and authority in Matthew's gospel - F. P. Viljoen (Acta Theologica)
Besides the strenuous relation of Matthew’s community with non-Christian kinfolk, his text also reveals an underlying conflict with Roman Imperial ideology. Herod, Antipas and Pilate specifically impersonate this foreign domination. Apparently these figures have unlimited power which leaves Jesus and his followers as exposed victims. Yet, on the deeper level of the text, Jesus ironically emerges as victor. He represents the Kingdom of God and ironically counters their unfair rule with his authority.